Factors inhibiting the psychological recovery process of children in conflict with the law - Puspitawati, Putri Marlenny; Subandi, Subandi; Adiyanti, Maria Goretti; Hiariej, Eddy Omar Sharif; Bulut, Solmaz (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Psychological assistance is crucial in recovering the psychological condition of children in conflict with the law. The City Government of Semarang, Indonesia has responded to this need with a school-based restorative justice program. This study aims to explore the factors that can hinder the psychological recovery process of children in conflict with the law during the implementation of the program. A qualitative approach was employed, based on case studies of three children in conflict with the law, with their significant others as participants. Case study data analysis techniques were employed, namely matching patterns, building explanations, finding model logic, and synthesizing cases. The results show that negative peer support, drug abuse, negative role models, emotional detachment, and negative stigma towards children in conflict with the law can be factors that hinder their psychological recovery process. The findings could provide the basis for practitioners in the preparation of psychological interventions that are relevant to the psychological recovery needs of children.